Biological markers as indicators for relapse in alcohol-dependent patients - Mundle, Götz; Ackermann, Klaus; Mann, Karl (Addiction biology, 1999)
Although biological markers such as carbohydrate-deficient transferrin (CDT), γ-glutamyl transferase (GGT) and mean corpuscular volume (MCV) have been used as indicators for heavy alcohol consumption and alcoholism little information is available on the utitlity of these markers in detecting relapses. In this study the value of the biological markers CDT, GGT and MCV was examined in monitoring an outpatient treatment programme for alcohol-dependent patients. In 163 male alcoholic patients CDT, GGT and mean corpuscular volume (MCV) were assayed at the beginning and after 6 months during the outpatient programme. All markers distingushed between relapsers and abstainers (p<0.01). The sensitivity for relapses was 55% for CDT, 50% for GGT and 20% for MCV. Combining all markers the sensitivity could be enhanced to 85%, with only a little loss of specificity (85%). The highest positive predictive value was 73% for CDT used as a single marker. The negative predictive value (CDT 93%, GGT 92%, MCV 88%) and the diagnostic efficiency (CDT 91%, GGT 87%, MCV 85%) of all markers were very high. These results indicate that CDT is the most efficient marker for alcohol relapses, followed by GGT. MCV seems to be a marker of second choice.